The Role of Sleep Quality as Mediator of Relationship between Workload and Work Fatigue in Mining Workers - Rosita Cahya Hidayanti; Sumaryono Sumaryono (Jurnal Psikologi, 2021)
The mining environment is a place to work with a high level of risk. One of the factors that cause work accidents in the mining area is work fatigue or work fatigue. The purpose of this study was to reveal the role of sleep quality as a mediator of the relationship between workload and work fatigue in mining workers in Indonesia. Research participants were mining workers who worked in the field with a 12-hour / day shift work system (n = 232). Measurements were made using 3 scales, namely Full Time Equivalent (FTE) for workload, Pittsburgh Sleep Quality Index (PSQI) for sleep quality, and Three-Dimensional Work Fatigue Inventory (3D-WFI) for work fatigue. The results of the analysis using bootstrapping 5000 showed that workload has a significant effect on the level of work fatigue which is mediated by sleep quality. High workload results in poor sleep quality and high levels of fatigue so that mining companies need to maintain the quality of sleep for field workers to minimize work accidents due to work fatigue.